Institutional entrepreneurship for responsible digital innovation: The case of corporate digital responsibility - Hannah Trittin-Ulbrich; Alexa Böckel (Creativity and Innovation Management, 2022)
How does responsible digital innovation become an accepted and desired innovation practice for businesses? Drawing on the case of Corporate Digital Responsibility (CDR), we study how institutional entrepreneurs across different fields construct CDR as an issue to legitimize corporate commitment to responsible digital innovation. Our qualitative study from Germany suggests that institutional entrepreneurship for responsible digital innovation entails the discursive, relational and material legitimation of responsible digital innovation through the issue of CDR. The findings of this study enrich institutional research on digital innovation by shedding light on the field-level construction of responsible digital innovation through Corporate Digital Responsibility. We further extend existing CDR frameworks by detailing the multi-stakeholder efforts that may shape a firm's approach to CDR, as well as by revealing additional topics associated with the issue. We highlight the theoretical and practical implications of our research.
Keywords: 330; corporate digital responsibility (CDR); digital innovation; institutional entrepreneurship; legitimacy; responsible digital innovation